Influence of Fuels and pH on the Dissolution Stability of Bifunctional PtRu/C Alloy Electrocatalysts - Kormanyos, Attila; Speck, Florian; Mayrhofer, Karl; Cherevko, Serhiy (ACS Catalysis, 2020)
The application of organic fuels in fuel cells is an attractive way to circumvent the major drawbacks of hydrogen as an energy carrier, yet catalysis is still a bottleneck for efficient oxidation. One of the most promising bifunctional anode catalysts is PtRu, which has proven to be the state-of-the-art electrocatalyst in alcohol oxidation processes. While plenty of works so far have addressed the activity and mechanism of oxidation reactions on PtRu, less is known about the influence of organic fuels on the stability during operation. In this contribution, the effect of isopropanol, methanol, ethanol, formic acid, ammonia, and carbon monoxide on the stability of carbon-supported PtRu was studied both in acidic and alkaline media. The scanning flow cell coupled to an inductively coupled plasma mass spectrometer (online ICP-MS) technique allowed the tracking of dissolution events that occurred during the applied electrochemical protocol in real-time. Our main conclusion is that PtRu/C remained stable in the operation range of fuel cells. In addition, if the upper potential limit was further increased PtRu/C was less stable in alkaline medium in which, if compared to acidic electrolyte, approximately 4-times higher Ru and 14-times higher Pt dissolution was measured in the absence of the studied fuels. The onset potential of dissolution was not affected by the presence of fuels (except CO), while dissolution rates were notably affected, most visibly in the case of isopropanol and ammonia in alkaline media and carbon monoxide in both acidic and alkaline media. The observed phenomena are briefly discussed underlining the necessity of more detailed and mechanistic studies to fully understand the reason behind dissolution processes in the presence of the investigated fuels.
CRIS-Team WoS Importer:2020-10-30